Copper-catalyzed preparation of N-aroylated sulfoximines from methylarenes. Issue 13 (3rd July 2017) - Hou, Anguo; Zhao, Zijian
ABSTRACT: A copper-catalyzed methodology for the preparations of N -aroylated sulfoximines from methylarenes was herein demonstrated. The transformation proceeded with the assistance of external oxidant tert -butyl hydroperoxide, requiring for no additional solvents or ligands. The good compatibility and high efficiency of the newly developed protocol were well described by 21 examples and up to 91% yields. Moreover, the protocol was proved by the control reactions to proceed through a radical pathway. GRAPHICAL ABSTRACT: